Perancangan Sistem E‑Procurement dengan Approval Berjenjang dan Penilaian Vendor Berbasis AHP di PT XYZ - Wahyudiyanta, Soni Agung; Fitra, Adi; Hidayat, Ade Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to design a web-based e‑procurement system integrated with a tiered digital approval feature and the Analytical Hierarchy Process (AHP) method as a decision support system for selecting transporter vendors. Data were collected through observation of procurement processes, interviews with relevant stakeholders, and pairwise comparison questionnaires to determine the AHP criteria weights. Vendor evaluation criteria include quality, price, service, reputation, and performance evaluation. The AHP calculation results show that quality (0.355) and price (0.289) are the criteria with the highest weights, with a consistency ratio (CR) of 0.00094 (<0.1), indicating that the judgments are consistent. Synthesis of the criteria and alternative weights produces Transporter C as the selected vendor with a total score of 0.374, followed by Transporter B (0.360) and Transporter A (0.265). The integration of AHP into the e‑procurement system enables vendor assessment and approval processes to be carried out digitally, objectively, and well documented, while the tiered approval mechanism speeds up the approval process and increases transparency. The designed system is expected to improve operational efficiency, accountability, and the quality of procurement decisions at PT XYZ.